Tinjauan Yuridis terhadap Hak dan Kewajiban Notaris dalam Era Digitalisasi: Analisis Undang-Undang Jabatan Notaris Nomor 2 Tahun 2014 dan Regulasi Tambahan - Retno Damayanti (Fakultas Hukum, Universitas Warmadewa, 2024)
The digitalization era has brought significant changes to various aspects of life, including the notary profession. This study aims to analyze the rights and obligations of notaries in the digital era based on the Notary Position Law No. 2 of 2014 (UUJN) and to identify regulatory gaps between UUJN and the Electronic Information and Transactions Law (UU ITE). The methodology used is a normative juridical approach, focusing on the analysis of positive law within UUJN and additional regulations related to digitalization. The findings reveal that UUJN currently does not fully accommodate the use of digital technology in notary practices, posing new challenges in data security, digital document authentication, and the validity of digital signatures. Furthermore, the weak integration between UUJN and UU ITE creates legal uncertainty for notaries in performing their duties in the digital age. The recommendations of this study include revising UUJN, establishing digital security standards, and providing specialized training for notaries to adapt to technological developments. With more adaptive regulations, it is hoped that the notary profession can effectively fulfill its function and maintain public trust.